2011
DOI: 10.1007/s10717-011-9292-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition and structural factors on the viscosity of borosilicate glasses and melts

Abstract: on the temperature curve of the viscosity in the 10 10 -10 4 Pa × sec range were established. The important effect of phase separation processes -liquation and crystallizationon the viscosity indexes in the temperature region of the transition from the plastic to the liquid state was demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In the past, the viscosity and structure relationships of B 2 O 3 -SiO 2 -based melts were investigated. [19][20][21][22][23][24][25] Shiraishi et al 20 found that the viscosity of Na 2 O-B 2 O 3 -SiO 2 (NBS) glass with SiO 2 /Na 2 O molar ratio of 1 or 2 first increased and then showed a decreased trend when B 2 O 3 content increased from 10 to 60 mol.% in the temperature range of 500-650 • C. This is due to the variations in amount of [BO 4 ] and [BO 3 ] in the glass melt. Zhang and Reddy 22 developed a viscosity model based on the melt structure to predict the NBS glass viscosity in the temperature range of 700-1200 • C. The model predictions were in good agreement with experimental data.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the past, the viscosity and structure relationships of B 2 O 3 -SiO 2 -based melts were investigated. [19][20][21][22][23][24][25] Shiraishi et al 20 found that the viscosity of Na 2 O-B 2 O 3 -SiO 2 (NBS) glass with SiO 2 /Na 2 O molar ratio of 1 or 2 first increased and then showed a decreased trend when B 2 O 3 content increased from 10 to 60 mol.% in the temperature range of 500-650 • C. This is due to the variations in amount of [BO 4 ] and [BO 3 ] in the glass melt. Zhang and Reddy 22 developed a viscosity model based on the melt structure to predict the NBS glass viscosity in the temperature range of 700-1200 • C. The model predictions were in good agreement with experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, boron anomalies, which were an abnormal change in the boron coordination structure with an increased B 2 O 3 content, were observed when SiO 2 /Na 2 O molar ratio was larger than 1. Mlima and Monteiro 21 and Levitskii and Papko 23 investigated the viscosity of NBS-based glass melt in the temperature range of 600-950 • C. It was found that the phase separation phenomenon between liquid and crystalline phases occurred in the melt, which increased its viscosity by 1-2 magnitudes. Ke et al 24 investigated the effect of alkali oxides on the structure and viscosity of xR 2 O (R represents Na and K)-1.1CaO-12.2B 2 O 3 -(83.7 − x)SiO 2 glass in the temperature range of 1100-1550 • C. It was found that the increased amount of Si-O-B bond leads to a high degree of melt interconnectivity and also improved the chemical stability of the melt when Na 2 O was less than 4 mol.%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 that the liquation phase separation that develops in the process of heat treatment of glasses with an increased B 2 O 3 concentration results in an increase of the viscosity indices in the 10 9 -10 4 Pa sec range.…”
mentioning
confidence: 98%